Botulinum Toxin Type A in the Treatment of Post-Stroke Spasticity - A Review of Current Evidence - Bajko, Julia; Ciszewski, Artur; Błażewicz, Juliusz; Bullmann, Agnieszka Irena; Chmielewski, Michał; Piskor, Michał; Kapusta, Kinga; Pazio, Klaudia; Strzalińska, Dominika; Kowalczuk, Maciej (Quality in Sport, 2026)
Background: Post-stroke spasticity (PSS) affects up to 42% of stroke survivors and significantly impairs rehabilitation. Botulinum toxin type A (BoNT-A) is a first-line pharmacological treatment that reduces muscle overactivity by inhibiting acetylcholine release at the neuromuscular junction. Aim: To summarize the current evidence on BoNT-A therapy for PSS, with emphasis on mechanisms of action, optimal administration timing, injection guidance, dosing, safety, and functional outcomes, to inform individualized neurorehabilitation. Material and Methods: A literature search of PubMed was conducted to identify relevant studies on the efficacy and safety of BoNT-A in adult patients with PSS (2013–2026). Records were screened by title, abstract, and full text against predefined inclusion criteria. Results: BoNT-A effectively reduces PSS with Grade A evidence, with the greatest benefit when administered early (3–12 weeks post-stroke). Imaging- or electrophysiology-guided injections improve precision. Therapeutic effects are temporary (approximately 12 weeks), requiring repeated administration. Adverse events are mild and uncommon, supporting a favorable safety profile. Conclusions: BoNT-A is a safe and effective treatment for PSS, particularly when initiated early and guided by imaging or electrophysiological techniques. Its impact on functional recovery remains variable, highlighting the need for individualized treatment strategies integrated with comprehensive rehabilitation programs.